METHODOLOGICAL SYSTEM OF PROFESSIONAL SELF-DEVELOPMENT OF FUTURE FOREIGN LANGUAGE TEACHERS (Scientific journal of the Fergana State University, 2024)
This article is about the professional self-development of future foreign language teachers, the reform and improvement of our country's continuous education system, the reform and improvement of the continuous education system of our country, and the perfect knowledge of a foreign language in accordance with the requirements of the world in the current rapidly developing period. level of education, introduction of advanced pedagogical and information technologies and improvement of educational efficiency have been raised to the level of state policy.